(untitled) (International Journal of Current Engineering and Technology, 2013)
The human locomotion with two legs is a periodic physical activity occurring by driving of the bones by muscles, which are stimulated by electrical signals transferred by neurons from the brain. Artificial limb is a mechanism for supporting the physically disabled by understanding the percentage of their disability and helps amputee get back to their normal functioning to a certain degree. This paper focuses on developing a control system drive to actuate the motorized assistive device. The driving circuit for the supervisory control of DC motors to lock and unlock the knee and hips for both limbs is designed and it should be synchronized such that the locomotion of both the hip and the knee is executed simultaneously. Here, 8051 microcontroller is used to control the 12V DC series motors for the desired position. The entire operation can be made closed loop with the help of feedback circuitry.